Drivers of Fiscal Sustainability: A Time-Varying Analysis for Portugal - António Afonso; José Carlos Coelho (Center for Economic Studies and ifo Institute (CESifo), 2023)
We assess the drivers of fiscal sustainability in Portugal during the period 1999Q4-2021Q4. We resort to expanding window and Schlicht (2003, 2021)'s time-varying approaches to construct the responses of government revenues to government expenditures and the responses of the primary government balance and the cyclically adjusted primary government balance (CAPB) to the debt-to-GDP ratio. Our results show the prevalence of a Ricardian fiscal regime in Portugal. If the (i-g) differential is positive, the positive response of the primary government balance to the debt-to-GDP ratio is amplified. An improvement in the external accounts, the increase in the European Commission's fiscal rules index and the extension of the debt maturity were beneficial for fiscal sustainability. Sovereign debt rating downgrades implied a posterior fiscal reaction that improves fiscal sustainability. Moreover, fiscal sustainability increased during the implementation of the international financial assistance program to Portugal, between 2011Q2 and 2014Q2.
Keywords: C23; H61; H63; E62; 330; fiscal sustainability; primary government balance; government debt; expanding window; time-varying; Portugal